HPV genotyping and p16/Ki-67 test significantly improve detection rate of high-grade cervical squamous intraepithelial lesion - Piotr Lewitowicz (Termedia Publishing House, 2019)
Introduction Liquid-based cytology allows to apply modern and specific analyses of hrHPV genotyping in p16/Ki-67 test. All of these together could raise accuracy ratio for high-grade squamous intraepithelial lesion above 90%. The purpose of this study was to evaluate the diagnostic accuracy of LBC, hrHPV testing, and p16/Ki-67 testing in diagnosis of high-grade cervical intraepithelial lesions.